Alternate Dosing Protocol for Magnesium Sulfate in Obese Women With Preeclampsia: A Randomized Controlled Trial. Issue 6 (December 2020) - Brookfield, Kathleen F.; Tuel, Kierstyn; Rincon, Monica; Vinson, Abbie; Caughey, Aaron B.; Carvalho, Brendan
Abstract : OBJECTIVE: To evaluate whether obese women need greater doses of magnesium sulfate to obtain therapeutic serum concentrations for eclamptic seizure prevention. METHODS: Women with preeclampsia and a body mass index (BMI) of 35 or higher were randomly allocated to either the Zuspan regimen of magnesium sulfate (4-g intravenous [IV] loading dose, then a 1-g/h infusion) or to alternate dosing (6-g IV loading dose, then a 2-g/h infusion). Women had serum magnesium concentrations obtained at baseline, as well as after administration of magnesium sulfate at 1 hour, 4 hours, and delivery. The primary outcome was the proportion of women who had subtherapeutic serum magnesium concentrations (less than 4.8 mg/dL) 4 hours after administration. A sample size of 18 women per group was planned to compare the proportion of women with subtherapeutic serum magnesium concentrations in each group. RESULTS: From July 12, 2016, to March 14, 2019, 89 women with preeclampsia were screened and 37 were enrolled: 18 to the Zuspan regimen and 19 to the alternate regimen. A significantly greater proportion of women administered the Zuspan regimen had subtherapeutic serum magnesium concentrations at 4 hours (100% [95% CI 59–100] vs 63% [95% CI 41–81]; P =.01) compared with women administered the alternate higher dose regimen. At 4 hours, mean concentrations were significantly higher in the alternate regimen group (3.53 mg/dL±0.3 [Zuspan regimen] vs 4.41±0.5 [alternate regimen]; P <.01). CONCLUSION: The alternate dosing regimen of a 6-g IV loading dose followed by a 2-g/h IV maintenance dose more reliably achieves therapeutic serum magnesium concentrations (as defined by a concentration of at least 4.8 mg/dL) in obese women with preeclampsia. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov, NCT02835339. Abstract : A magnesium sulfate regimen of a 6-g intravenous loading dose followed by a 2-g/h maintenance dose more reliably achieves a therapeutic serum magnesium concentration in obese women with preeclampsia.